Systems Biology Approach to Deciphering the Multilevel Impact of Pollution on Animal Physiology / Review Article (The Peerian Journal, 2025)
Pollution has strongly increased during the past decades due to intensive industrial activities, expansion of agriculture and urban areas, as well as increasing use of chemicals, heavy metals, POPs, and other novel industrial pollutants like micro plastics, these can affect health in animals and ecosystems on levels ranging from molecular changes in genes and proteins up to disturbances in metabolism and organ functions, including behavioral and social changes, which again may impede survival, reproduction, and biodiversity. Traditional single measure approaches cannot conceptualize the complexity and timecourse variability of the biological response to pollution. Systems biology allows a holistic perspective on such effects by way of integrated molecular, proteomic, metabolic, tissuelevel, and behavioral data. It will be able to deliver early biomarkers, identify adaptive and compensatory mechanisms used by organisms under stress, and give more reliable estimates of risks for the environment. Systems biology will continue to enable effective strategies in environmental protection, including those relevant to environmental pollutants, sentinel species as bioindicators, and predictive modeling of new or chronic pollutants. This approach faces several significant challenges, including the complex nature of both the data and biodiversity, the limited availability of high-resolution environmental data, the requirements for advanced computational tools, and the need for integrated, multi-level models. The study concluded that animal health and ecosystem stability are compromised at all levels of environmental pollution.